QUALITY OF COMMERCIAL FROZEN BOILED CLAM MEAT - VARMA, P R.G; IYER, T S.G; MATHEN, CYRIAC (Fishery Technology, 2017)
The bacterial quality and sand content of commercial frozen boiled clam meat are discussed. In general the commercial frozen boiled clam meat belonging to the Villorita cyprinoides sp. coUected from Cochin are highly contaminated with faecal indicator and pathogenic organisms than that belonging to the Katelysia opima sp. coUected from Quilon. The studies also show that the bacterial quality of frozen boiled clam meat can be improved by enforcing better hygienic and sanitary practices